2013
DOI: 10.1371/journal.pone.0051309
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin Potentiates Rhabdomyosarcoma Radiosensitivity by Suppressing NF-κB Activity

Abstract: Ionizing radiation (IR) is an essential component of therapy for alveolar rhabdomyosarcoma. Nuclear factor-kappaB (NF-κΒ) transcription factors are upregulated by IR and have been implicated in radioresistance. We evaluated the ability of curcumin, a putative NF-κΒ inhibitor, and cells expressing genetic NF- κΒ inhibitors (IκBα and p100 super-repressor constructs) to function as a radiosensitizer. Ionizing radiation induced NF-κΒ activity in the ARMS cells in vitro in a dose- and time-dependent manner, and upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…Curcumin (diferuloylmethane), a hydrophobic polyphenol molecule extracted from turmeric (Curcuma longa Linn), has a wide range of pharmacological activities, including anti-inflammatory, antioxidant and anticancer properties (9). Curcumin exerts a suppressive effect on NF-κB activity in various biological contexts (10,11). For instance, curcumin has been found to enhance the chemosensitization of colorectal cancer cells to conventional chemotherapeutic agents, such as 5-fluorouracil through inhibition of NF-κB and Src protein kinase signaling pathways (10).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin (diferuloylmethane), a hydrophobic polyphenol molecule extracted from turmeric (Curcuma longa Linn), has a wide range of pharmacological activities, including anti-inflammatory, antioxidant and anticancer properties (9). Curcumin exerts a suppressive effect on NF-κB activity in various biological contexts (10,11). For instance, curcumin has been found to enhance the chemosensitization of colorectal cancer cells to conventional chemotherapeutic agents, such as 5-fluorouracil through inhibition of NF-κB and Src protein kinase signaling pathways (10).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, searching for new radiosensitizers is of great importance. Phytochemicals have drawn wide attention as promising radiosensitizers in the course of radiotherapy (20)(21)(22)(23). [6]-Gingerol has demonstrated potential chemopreventive ability in various cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the mechanisms and the signaling pathways associated with regulation of resistance to radiation is crucial in development of approaches to overcome this. Previous research has focused on identifying tumor-specific sensitizing agents to enhance radiotherapy, and multiple studies have demonstrated the effect of many natural compounds, including curcumin and berberine, in improving sensitivity of cancer cells to radiation (31)(32)(33). A previous study has also reported the antitumor effects of paeonol on human lung adenocarcinoma cells (34).…”
Section: Discussionmentioning
confidence: 99%